Ethical dilemmas in palliative care: a study in Taiwan. Issue 5 (1st October 2000) - Chiu, Tai-Yuan; Hu, Wen-Yu; Cheng, Shao-Yi; Chen, Ching-Yu
Abstract : Objectives—To investigate the incidence and solution of ethical dilemmas in a palliative care unit. Design—Health care workers recorded daily all dilemmas in caring for each patient. Setting—Palliative care unit of National Taiwan University Hospital in Taiwan. Patients—Two hundred and forty-six consecutive patients with terminal cancer during 1997-8. Main measurement—Ethical dilemmas in the questionnaire were categorised as follows: telling the truth; place of care; therapeutic strategy; hydration and nutrition; blood transfusion; alternative treatment; terminal sedation; use of medication, and others. Results—The type and frequency of ethical dilemmas encountered were: place of care (33.3%); truth-telling (32.1%); hydration and nutrition (25.2%); therapeutic strategy (24.8%), and use of medication (19.1%). Ethical problems relating to the place of care and to therapeutic strategy were unlikely to be solved with increased hospital stay and some ethical dilemmas remained unsolved even in the final week in hospital, including place of care (23.2%), truth-telling (17.1%) and therapeutic strategy (11.4%). Problems of truth-telling occurred in nearly half (42.6%) of patients over sixty-five-years-old. Conflicts about blood transfusion were experienced in all patients below 18-years-old, and the dilemmas concerning the place of care occurred most frequently with head and neck cancer patients (43.8%). Conclusions—The solution of ethical dilemmas required refocusing by medical professionals on the importance of continuing communication. Improved ethical training for professionals would contribute to solving the moral dilemmas of palliative care.